Digital Transformation of Self Assessment System on Final Income Tax in Small Micro Business and Medium at Pratama Tax Office of West Bekasi - Dwikora Harjo; Novianita Rulandari; Aprilia Alfani; Raveedhan Syachlin (Ilomata International Journal of Tax and Accounting, 2021)
The phenomenon in this study is related to the self-assessment system for taxpayers in the context of the Government Regulation Number 23 of 2018 implementation, where many Micro, Small, and Medium Enterprises (MSMEs) do not understand tax administration and consider taxation obligations to be complicated. The purpose of this study is to find out and analyze the self-assessment system for final tax income on MSMEs at the Pratama Tax Office of West Bekasi in 2018-2020 along with the obstacles and efforts made by the tax office regarding the self-assessment system. This research is descriptive research with a qualitative approach. Data analysis was carried out using qualitative methods. The results of this study indicate that the implementation of Government Regulation Number 23 of 2018 regarding the self-assessment system has not fully run as expected. In terms of registration and reporting, taxpayers have complied with these regulations, but in calculating and paying their taxes they have not fully complied with the rules. The obstacles include MSMEs who are still unfamiliar with taxes and do not understand IT, regulators who are still having trouble supervising the taxation activities of taxpayers, and the lack of tax dissemination and counseling. As a result, the MSME tax contribution has decreased during 3 years due to the decline in the MSME Tax rate. The average contribution of MSME tax revenue at the Primary Tax Office of West Bekasi is 8.77% of final income tax receipts.